Bean leafroll virus (BLRV) in Argentina: molecular characterization and detection in alfalfa fields - Trucco, Veronica Milagros; De Breuil, Soledad; Bejerman, Nicolas Esteban; Lenardon, Sergio Luis; Giolitti, Fabian (Springer, 2018)
Alfalfa (Medicago sativa L.) is the main forage crop in Argentina and plays an essential role in the animal production chain, but it can be negatively affected by many factors, such as viral diseases. Here, we report the presence of Bean leafroll virus infecting alfalfa (BLRV-Arg), its distribution on alfalfa fields and its complete genome sequence. BLRV-Arg showed a prevalence of over 50 % and a wide distribution in Argentine alfalfa fields. The BLRV genome of the Manfredi isolate (Manfredi BLRV-Arg) is 5884 nucleotides in length, with a genome organization similar to that already reported for this virus. The complete nucleotide sequence or selected genes were subjected to sequence comparisons. Manfredi BLRV-Arg had more than 96 % nucleotide and amino acid sequence identities, both for complete genome sequence and ORFs, with those of the two full-length genome sequences available in GenBank. The complete CP sequences of Manfredi BLRV-Arg showed an identity percentage over 98 % at nt and deduced aa level when were compared with those of the other CP complete sequences available in GenBank. This is the first evidence for the presence of BLRV in Argentina, its geographical distribution in alfalfa production areas and the complete genome sequence of an isolate from alfalfa as natural host.